Participation of The People in The Preparation of Local Development Plans of Donmasang Sub-district Administrative Organization, Mueang Supanburi District in Supanburi Province - Toprasee, Surasak; Seangyai, Kanyanat; Charoenphon, Prapatson (Journal of Faculty of Humanities and Social Sciences Thepsatri Rajabhat University, 2023)
This research aimed to study 1. the level of people participation factor, 2. the level of people participation, 3. to compare public participation, and 4. the relationship between factors and public participation in the preparation of local development plans. It is survey research. The sample comprised 358 people living in the Don Masang Subdistrict Administrative Organization. The instrument used for data collection was a questionnaire. Descriptive statistics were used to analyze and were analyzed using descriptive statistics, i.e., frequency, percentage, MEAN, and standard deviation. The hypothesis was tested by inferential statistics – One-way ANOVA and Pearson’s correlation coefficient. The findings revealed the following. 1. The factors of public participation in the preparation were found at a high level. After item analysis, motivation was the item with the highest MEAN, followed by benefits and attitude as the one with the lowest MEAN. 2. The public participation was generally found at the high level. After item analysis, the operation was the item with the highest MEAN, followed by a decision and sharing benefits was the one with the lowest MEAN 3. Personal factors such as sex, age, education, marital status, occupation, and income did not significantly affect difference in public participation in the preparation of local development plans at the .05 level. 4. The factors, i.e., attitude, benefits, motivation, and opportunity, were positively related at the moderate level to public participation in the preparation of local development plans at 0.01 significance level.